The Validity of The Absence of An Indonesian Translation in International Business Contracts - Septi Songgo Langit, Shyntaulloh; Sulistiyono, Adi; Torry Satriyo Kusumo, Ayub (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
An agreement is a legal act between two or more parties who bind themselves to one another. Indonesian law requires agreements to be drafted in the Indonesian language, as stipulated in Law Number 24 of 2009 and Law Number 2 of 2014. However, Supreme Court Circular Letter (SEMA) Number 3 of 2023 states that the absence of the Indonesian language in an agreement shall not automatically render the agreement null and void, creating a potential conflict with the contractual validity requirement of a lawful cause. This study aims to analyze the legal implications of agreements drafted without an Indonesian-language version in light of SEMA Number 3 of 2023. The research serves for the preparation of a Master of Notarial Law thesis at Sebelas Maret University, providing deeper insight and understanding of the legal issues involved. Using a normative legal research method with statutory and conceptual approaches, this study concludes that the absence of the Indonesian language in agreements may result in nullity by operation of law, violates Article 31 of Law Number 24 of 2009 and Article 43 of Law Number 2 of 2014, which explicitly mandate the use of Indonesian. Such violations affect the objective validity requirement of a lawful cause. This normative inconsistency has broader implications for Indonesia’s economic stability, as legal certainty supports economic growth. The obligation to use the Indonesian language is reinforced by Article 7 of Law Number 12 of 2011 concerning the hierarchy of laws, applying the principle of lex superior derogat legi inferiori.